Food Solutions Rheumatism and Arthritis : Recipes and Advice to Stop the Pain - Westcott, Patsy (London Hamlyn, 2005)
For many sufferers of rheumatism and arthritis, debilitating pain becomes a part of everyday life. This book shows how a change of diet can help to alleviate these conditions. Over 70 delicious recipes are included, making it easy to follow the dietary advice and still enjoy exciting food
Include Glossary and Index
Keywords: Rheumatism--Diet therapy -- Arthritis--Diet therapy